Environmental Cost and Face of Agriculture in the Gulf Cooperation Council Countries Fostering Agriculture in the Context of Climate Change - Shahid, Shabbir A.; Ahmed, Mushtaque; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This volume presents the outcome of an Agriculture Workshop organized by the Gulf Research Centre Cambridge (GRCC), and held at Cambridge University, UK during the Gulf Research Meeting 11-14 July 2012. Co-directed by the editors, the workshop, entitled “Environmental Cost and Changing Face of Agriculture in the Gulf States” was attended by participants from Australia, Bahrain, India, Kuwait, Oman, Saudi Arabia, Turkey, UAE, UK, and Morocco. These scientists, educators, researchers, policy makers and managers share their experience in agriculture in the Gulf States, with the aim of helping to improve agriculture production and thus bridge the gap between local production and the food import. The papers gathered here were presented at the workshop, and have all passed through rigorous peer review by renowned scientists. The diverse papers present various aspects of agriculture production in the evolving face of climate change and dwindling water resources in the region. The book covers topics such as the prospects of agriculture in a changing climate; the potential of climate-smart agriculture; the impact of food prices, income and income distribution on food security; improved efficiency in water use; challenges in using treated wastewater in agriculture; investment in foreign agriculture and agricultural research and development. The papers span the nations of the Gulf Cooperation Council, with specific case studies set in Oman, Bahrain and Kuwait.
Chapter 1 Changing Face of Agriculture in the Gulf Cooperation Council Countries -- Chapter 2 Achieving Food Security in a Changing Climate: The Potential of Climate-Smart Agriculture -- Chapter 3 Prospects of Agriculture in the State of Kuwait-Constraints and Opportunities -- Chapter 4 Improved Water Use Efficiency is a Key Practice to Sustain Food Production in the GCC Countries -- Chapter 5 The Potential of Transforming Salalah into Oman’s Vegetable’s Basket -- Chapter 6 Climate Changes, Water Scarcity and Food Security Complex: A case Study from Bahrain -- Chapter 7 Opportunities and Challenges of Using Treated Wastewater in Agriculture -- Chapter 8 Investments in Foreign Agriculture as a Gulf State Food Security Strategy: Towards Better Policy -- Chapter 9 Impact of Food Prices, Income and Income Distribution on Food Security in Oman Hemesiri -- Chapter 10 Agricultural Research and Development and Food Security in the Gulf Region -- Index.
Keywords: Environment; Agriculture; Water pollution; Climate change; Water quality; Environment, general; Agriculture; Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution; Climate Change; Climate Change/Climate Change Impacts; Water Quality/Water Pollution